Dronning Maud Land: der ingen skulle tru at det var fjell ... - Engeland, Sveinung; Engeland, Sveinung (Høyde over havet : hvordan fjellene våre ble målt og satt på kartet, 2021)
Keywords: Dronning Maud Land; ekspedisjoner; geografi; kartlegging; oppdagelsesreiser

Roald Amundsens Sydpolsexpedition 1909-1912 - Norén, Karl-Gunnar (Polarexpeditionernas proviant: 1872-1949, 2021)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ernæring; oppdagelsesreiser

The return of the South Pole sled dogs : with Amundsen’s and Mawson’s antarctic expeditions - Tahan, Mary R. (Springer Nature, 2021)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; sledehunder; trekkhunder

Roald Amundsen’s sled dogs : the sledge dogs who helped discover the South Pole - Tahan, Mary R (Springer, 2019)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; sledehunder; trekkhunder

Kapten Roald Amundsen: I vargskinnspäls och textil. Blir först på Sydpolen - Norén, Karl-Gunnar (Polarfararnas kläder : på liv och död, 2018)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; polarekspedisjoner; utstyr

Carsten Borchgrevink and the Southern Cross Expedition, 1898-1900 - Riffenburgh, Beau; Kløver, Geir O (Red.) (The Fram Museum, 2017)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

C.A. Larsen : explorer, whaler & family man - Riffenburgh, Beau (Red.); Kløver, Geir O (Red.) (The Fram Museum, 2016)
Keywords: Antarctic ekspedisjonen; Antarktis; Carl Anton Larsen; D/S Antarctic; D/S Jason; Jason ekspedisjonene; Weddellhavet; hvalfangere; hvalfangst; oppdagelsesreiser; polarforskning

The canine explorers – the sled dogs who helped Roald Amundsen reach the South Pole - Tahan, Mary R (Journal of Antarctic Affairs, 2016)
One hundred Greenland dogs were purchased by Roald Amundsen from the Royal Greenland Trading Company in September 1909 ostensibly for a North Pole expedition, but secretly to use to reach the South Pole. Amundsen considered the dogs “equipment”. He was a complicated character in a very different time. And he compulsively pursued his mission. His actions perhaps are seen differently from the 21st century perspective and in light of our evolving attitude toward animals, especially dogs. This paper presents the facts of what happened concerning the sled dogs, using Amundsen’s own statements in his books, diaries, and letters, as well as the expedition members’ journal entries and personal letters. It focuses on the dogs who made Amundsen’s exploration possible, and who helped humankind discover the final undiscovered part of our world. Amundsen began his Norwegian expedition with 97 sturdy canine souls, who were taken on board the Fram near the coast of Kristiansand in August 1910. Through births and deaths on the ship during their five-month journey south, the dogs’ number swelled to 116 upon arrival in Antarctica. Adults and puppies alike withstood the roller-coaster ride of the Fram on the ocean waters, the heat of the tropics near the equator, and the freezing winter of Antarctica. Taking into account the birth of puppies on the ship and at their Antarctic home Framheim, the actual number of dogs involved in this significant moment in history doubles to over two hundred. But, after initially nurturing and protecting the dogs, Amundsen proceeded to cull them throughout the expedition, slaughtering those he deemed unnecessary or weak, and destroying those who had served their purpose. Amundsen began his South Pole trek in October 1911 with 52 brave canines, and returned with 11, as a result of unnatural, forced attrition. The dogs were nearly starved; at times when they were fed, it was the flesh of their fallen comrades they were given to line their empty stomachs. And yet the dogs all performed their roles brilliantly, even when death was their reward. The sled dogs were the heart and power of the South Pole expedition. The intent of this article is to shine a light on the dogs’ population, accomplishments, and sacrifices, and to give them their due recognition and place in history.
Publisher: Agenda Antártica. Antarctic and Southern Ocean Coalition (ASOC)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; sledehunder; trekkhunder

Frozen voices: Women, silence and Antarctica - Blackadder, Jesse (Antarctica : music, sounds and cultural connections, 2015)
This chapter explores a different kind of Antarctic silence: the silencing of certain stories and voices. It’s the silence of the earliest female travellers to Antarctica.The voices of the earliest female travellers are silent and their stories remain untold, partly because there’s no place for them in the dominant Antarctic narrative of exploration and conquest. Reimagining them through fiction is one way — though with potential pitfalls — to ‘unfreeze’ those stories.
Keywords: Antarktis; Nordmenn; ekspedisjoner; kvinner; oppdagelsesreiser

The great white silence : den offisielle filmen om Robert Falcon Scotts sydpolekspedisjon og en vurdering av ekspedisjonen - Lund, Vidar (Maritimt Magasin Historie, 2015)
Publisher: Commentum Forlag Place: Oslo
Keywords: Antarktis; Robert Falcon Scott; Sydpolsekspedisjonen; oppdagelsesreiser

Leadership lessons from the race to the South Pole : why Amundsen lived and Scott died - O'Connell, Fergus (Praeger, 2015)
A project management expert identifies methods for running any project successfully based on lessons learned from the exploits of two storied explorers.
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser

Polare strøk. Skippere og fangstfolk. Den nye tid - Aasheim, Stein P. (Norske eventyrere, 2014)
Keywords: Antarktis; Bernt Balchen; Carl Anton Larsen; Carsten Borchgrevink; Nordmenn; Tryggve Gran; geografi; historie; oppdagelsesreiser; polarekspedisjoner

[Bir kəşfiyyatçı kimi həyatım] - Amundsen, Roald (Alatoran, 2014)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

Kanten av isødet - Blackadder, Jesse; Berg, Ellen Karine (Juritzen, 2014)
Roman om tre kvinner fra Sandefjord og kampen om å komme først til Antarktis. Sandefjord 1930. Ingrid er gift med byens hvalkonge, Lars Christiansen. Hun har drømt om å reise til Antarktis siden hun var barn, og nå har ektemannen lovet å ta henne med på en av hvalbåtene. Betingelsen er at hun har med seg en kvinnelig ledsager, og den deprimerte enken Mathilde blir motvillig rekruttert. Samtidig sitter Lillemor Rachlew i London og ønsker mest av alt å bli første kvinne i Antarktis. Hun får høre om reisen til Ingrid, og får lurt seg med på samme båt rett før den forlater Cape Town. Kappløpet mot et livsfarlig isøde er i gang, og reisen vil bli skjebnesvanger for alle de tre kvinnene. Denne fascinerende romanen er basert på virkelige hendelser. Vi blir tatt med til 1930-årenes Sandefjord, til hvalfangstindustriens gullalder, og blir kjent med tre kvinner som kjempet ikke bare for sin selvstendighet, men også for sin plass i historien.
Keywords: Antarktis; Nordmenn; ekspedisjoner; fortellinger; kvinner; oppdagelsesreiser

The Third Expedition, 1910-1912: Antarctica and the Southern Ocean - Johnson, Charles W (Ice ship : the epic voyages of the polar adventurer Fram, 2014)
Keywords: Antarktis; Fram (skip); Roald Amundsen; Sydpolsekspedisjonen; Sørpolen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

Women, whales and Antarctica - Blackadder, Jesse (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Antarktis; første landgang; historie; kvinner; oppdagelsesreiser

Sydpolfarerne Per Savio og Ole Must : liv i grenseland - Sandholm, Unni Aas (Temahefter Aas Sandholm, 2013)
Keywords: Antarktis; Southern Cross; Sydpolen; ekspedisjonen; oppdagelsesreiser; overvintring; polarekspedisjoner; samer

Tryggve Gran : is, luft og krig - Simonsen, Anne Hege (Cappelen Damm, 2013)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; oppdagelsesreiser; polarområdene

Roald Amundsen: Forsker eller grobian? - Blix, Arnoldus Schytte (Nordisk tidskrift för vetenskap, konst och industri, 2012)
Roald Amundsens (1872-1928) liv og bedrifter er fremstilt i en rekke biografier, men det er oppdageren og eventyreren som blir tillagt mest vekt, mens vitenskapsmannen og forskeren tidvis underkjennes. Professor i arktisk biologi ved Universitetet i Tromsø, Arnoldus Schytte Blix, er kritisk til mye av det biografiske arbeidet som er gjort, og mener det er et åpent spørsmål om kontorhistorikere og journalister har noen reell mulighet til fullt ut å forstå Roald Amundsens situasjon og reaksjoner. Artikkelen er basert på et foredrag med en rekke illustrasjoner i Det Norske Videnskabs-Akademi, 17. november 2011.
Publisher: Föreningen Norden Place: Stockholm
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; biografier; oppdagelsesreiser

The Mapping of Antarctica - Pedersen, Jakob Søndergård; Curtis, Philip (The Map House, 2012)
Keywords: Antarktis; ekspedisjoner; kart; kartlegging; kartografi; oppdagelsesreiser

Of reindeer, ponies and automobiles : Roald Amundsen and the Norwegian bid for the South Pole - Turney, Chris (1912 : the year the world discovered Antarctica, 2012)
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Veivisere under sydkorset - Walsøe, Jan Oskar (Sophie Borchgrevink Nordrum og Ivar O. Nordrum, 2012)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; Sydpolen; ekspedisjonen; ekspedisjoner; kartlegging; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Bjaaland, Olav (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Belgica. South Pole. The Heroic Dogs. Darkness and Light. Amundsen and Byrd - Cox, Lynne (South with the sun : Roald Amundsen, his polar explorations, and the quest for discovery, 2011)
Keywords: Antarktis; Roald Amundsen; Sydpolekspedisjonen; Sydpolen; oppdagelsesreiser; polarekspedisjoner; sledehunder

Sydpolsekspedisjonen 1910-1912 - Gjertsen, Hjalmar Fredrik (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Hassel, Sverre (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Johansen, Hjalmar (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Das Eis und der Tod : Scott, Amundsen und das Drama am Südpol - Jostmann, Christian (Beck, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Der Wettlauf zum Südpol : das grösste Abenteuer der Geschichte - Knopp, Guido; Sporn, Mario; Schnier, Marten (Bertelsmann, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Race to the end : Scott, Amundsen and the South Pole - MacPhee, Ross D E (The Natural History Museum, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1914 - Nilsen, Thorvald (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; oseanografi; polarområdene

Le tombeau des glaces : duel mortel pour le pôle - Pierre, Marc (Dorval, 2011)
Publication Title: Collection Grandes aventures polaires
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Prestrud, Kristian (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1914 - Schröer, Adolf Hermann; Hansen, Ludvig; Rønne, Martin; Hanssen, Helmer; Kutschin, Aleksandr; Wisting, Oscar; Stubberud, Jørgen; Doxrud, Christian; Stubberud, Jørgen; Hansen, Ludvig; Rønne, Martin (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Amundsen, Roald (Frammuseet, 2010)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

The South Pole expedition 1910-1912 - Amundsen, Roald (Frammuseet, 2010)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Roald Amundsens sydpolsferd (1910-1912) = Roald Amundsen's South Pole expedition (1910-1912) - Amundsen, Roald; Diesen, Jan Anders; Lund, Harald Østgaard (Norsk filminstitutt, 2010)
Publication Title: Roald Amundsen's South Pole expedition (1910-1912) Place: Oslo
Keywords: Antarktis; Fram (skip); Norge; Sydpolen; Sydpolsekspedisjonen; dokumentarfilmer; ekspedisjonsfilmer; oppdagelsesreiser; polarområdene

Race for the South Pole : the expedition diaries of Scott and Amundsen - Amundsen, Roald; Scott, Robert Falcon; Bjaaland, Olav; Huntford, Roland (Continuum, 2010)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; kjeldeskrift; oppdagelsesreiser; polarområdene; polferder

Antarctic pioneers : the voyage of the Belgica 1879-99 - Kløver, Geir O (Red.) (The Fram Museum, 2010)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; ekspedisjoner; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Roald Amundsen: Conqueror of the South Pole - Thyvold, Hans Olav (Font forl., 2010)
ROALD AMUNDSEN (1872-1928), norsk oppdager, polfarer og nasjonalhelt. Det første mennesket som fant og seilte gjennom Nordvestpassasjen, og førstemann til å sette fot på Sydpolen. Norges nasjonalarv er en serie gjennomillustrerte bøker som presenterer våre viktigste og mest kjente nasjonale ikoner. De enkeltstående bøkene tar for seg betydelige skikkelser innenfor kunst og litteratur, vitenskap, idrett og samfunnsliv, men også landets mange naturperler, samt sentrale historiske epoker og kulturuttrykk. Hver for seg gir bøkene en oppdatert innføring for lesere som vil gjøre seg bedre kjent med et gitt tema.
Publication Title: Norwegian Heritage
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Belgicaekspedisjonen 1897-1899 : den første overvintring i Antarktis - Amundsen, Roald; Kløver, Geir O. (Red.) (Frammuseet, 2009)
Publication Title: Roald Amundsens dagbøker
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; dagbok; ekspedisjoner; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

[Im kyank’y vorpes beverrayin hetazotogh] - Amundsen, Roald; Movsisyaně, Suren (Toner, 2008)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

Vår glemte polarhelt : Carsten Borchgrevink og Southern Cross-ekspedisjonen 1898-1900 - Vogt, David (Aschehoug, 2008)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Nordmenn; Ole Must; Per Savio; Southern Cross; Sydpolen; biografier; ekspedisjonen; ekspedisjoner; oppdagelsesreiser; polarforskning; polarområdene; samisk

På nåde over Antarktis : verdens lengste skitur : 4804 km - Gjeldnes, Rune (SEAL Adventure, 2007)
Keywords: Antarktis; geografi; oppdagelsesreiser; polarekspedisjoner; reiser; reiseskildringer

Henrik Bull, the Antarctic Exploration Committee and the first confirmed landing on the Antarctic continent - McConville, Andrew (Polar Record, 2007)
Publisher: Cambridge University Press
Keywords: Antarktis; Carsten Egeberg Borchgrevink; D/S Antarctic; Henrik Johan Bull; Kapp Adare; Leonard Kristensen; Rosshavet; Victoria Land; ekspedisjoner; forskning; første landgang; oppdagelsesreiser

Whalers and explorers; logistic assistance provided to people whose work, and indeed survival, depended on the whalers - Headland, Robert Keith (Whaling and History II : new perspectives, 2006)
Keywords: Antarktis; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Ekspedisjoner og begivenheter - Barr, Susan (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; oppdagelsesreiser; polarfarere

Amundsen og hans aeronauter - Berg, Roald (Norsk polarhistorie, 2004)
Keywords: Antarktis; Norvegia ekspedisjoner; flyging; flyvere; oppdagelsesreiser

The race for the South Pole: Robert Scott and Roald Amundsen (1911-12) - Fleming, Fergus (Off the map : tales of endurance and exploration, 2004)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser; polareksspedisjoner

Å spise kirsebær med de store - Friedman, Robert Marc (Norsk polarhistorie, 2004)
Keywords: Antarktis; Dronning Maud Land; Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; oppdagelsesreiser

"En æressag for vor nation" - Fulsås, Narve (Norsk polarhistorie, 2004)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; oppdagelsesreiser

De tre store - Næss, Atle (Norsk polarhistorie, 2004)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

Pionerforskning i Sørishavet. Kappløpet mot Sydpolen - Berg, Kåre; Brenna, Åsta (Polarheltene : norske pionerer i Arktis og Antarktis, 2003)
Keywords: Antarktis; Carl Anton Larsen; Carsten Borchgrevink; Roald Amundsen; Sydpolen; biografier; oppdagelsesreiser; polarekspedisjoner; polarflyving; polarforskning; polarhelter

Pioneering exploration in the Antarctic Ocean. The race for the South Pole - Berg, Kåre; Brenna, Åsta; Aase, Jean (Heroes of the polar wastes : pioneer Norwegian explorers in the Arctic and the Antarctic, 2003)
Keywords: Antarktis; Carl Anton Larsen; Carsten Borchgrevink; Roald Amundsen; Sydpolen; biografier; oppdagelsesreiser; polarekspedisjoner; polarflyving; polarforskning; polarhelter

Antarctica - Sale, Richard (Polar reaches : the history of Arctic and Antarctic exploration, 2002)
Keywords: Antarktis; Sydpol; Sydpolsekspedisjonen; ekspedisjoner; fangst; forskning; hvalfangere; oppdagelsesreiser; polarområdene

Antarctica - Sale, Richard (To the ends of the Earth : the history of Polar exploration, 2002)
This text provides an insight into the early history of the Polar regions, and tells the stories of Man's first exploration of the Arctic and Antarctic, and subsequent expeditions. The history of individual Polar expeditions has been told many times, but usually only as personal accounts of individual adventures. This misses the overall context of polar exploration - why the British depended on ponies, or plant-eating animals (on the only continent where plants don't grow), why Franklin's men perished when the local Eskimos were eking out an existence around them (and reporting Franklin's demise), and why the Scandinavians were always better than anybody else. The first map of Antarctica was produced in 1556 - the Vikings visited the Arctic 1,000 years before. In 2001, the US Base at the South Pole is manned 365 days a year. The book tells the whole story of how the two last wildernesses, at either end of the world, were discovered, conquered and tamed.
Keywords: Antarktis; Belgica ekspedisjon; Carsten Egeberg Borchgrevink; Nordmenn; Norge; Roald Amundsen; Southern Cross; Sydpolsekspedisjonen; ekspedisjonen; historie; hvalfangst; oppdagelsesreiser; pelagisk; polareksspedisjoner

Henryk Johan Bull (1893-1895). Carsten E. Borchgrevink (1898-1900). Roald Amundsen (1910-1912) - Rosove, Michael H (Let heroes speak : Antarctic explorers, 1772-1922, 2000)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Henrik Johan Bull; Roald Amundsen; Sydpolen; biografier; oppdagelsesreiser; polarekspedisjoner